Design and Development of "Red Song Liao Liang, Silver Age Shining" Senile Singing Course - Ren, Zihan; Hu, Yi; Wamg, Jiye (Pacific International Journal, 2024)
This study presents the design and development of "Red Song Loud and Clear, Silver Age Shining," a singing course created specifically for elderly participants at Taizhou College of Nanjing Normal University. With a focus on promoting mental health, emotional expression, and social engagement through music, the course integrates "red songs," which hold significant cultural value in China. Through interactive sessions that incorporate vocal training, multimedia aids, and group activities, the course aims to address mental health challenges commonly faced by the elderly, including isolation, depression, and stress. The course structure was informed by a thorough needs assessment, analysis of existing singing programs, and feedback from stakeholders. Evaluation results indicate significant improvements in participants’ social well-being, emotional resilience, and cognitive engagement, underscoring the potential of culturally resonant music programs in elderly education.